Rapid stabilisation of hemic peat using melamine urea formaldehyde polymer resin by soil column method - Mohd Daud, Mohd Nazrin (2019)
Generally, organic soil such as peat always associated with low strength properties and high compressibility behaviour that causes unfavourable load – settlement characteristic for any construction purpose. Conventionally, it is common to avoid these problematic soils area or in some cases soil replacement is used as a normal practice. However due to certain unavoidable circumference, rapid application method of soil stabilisation may attractively useful for rapid construction purposes, particularly during emergency or contingency in which time is greatly crucial. In this study, hemic peat soil has been stabilised using polymer resins such as melamine urea formaldehyde (MUF) polymer resins for the application of soil column reinforcement method. For this purpose, peat medium has been reinforced using powdered MUF (MUF-P) for rapid strength gains within maximum 72 hours or 3 days of curing period. Preliminary, strength development of treated peat soil has been studied using unconfined compressive strength (UCS) test. Physical properties of untreated and treated peat are among other important characterisation, as well as other mechanical properties that were also studied in this research. The results of laboratory test were important as input parameters for physical modelling test and finite element analysis. Physical modelling of scale-down laboratory model of the footing for area replacement ratio, α = 9.4%, 14.1% and 23.6% with various depths of 100 mm, 150 mm and 200 mm has been developed and simulated for load bearing test. Soil columns were treated with designated maximum MUF-P proportion under wet curing method before tested under load test at various depths for end- bearing foundation application. Additionally, finite element modelling using PLAXIS software was conducted for validation purpose. Parametric study such as bearing capacity and settlement reduction ratio had also been conducted accordingly. Overall, the result in this study has suggested that the stabilisation of peat soil using MUF-P resin polymer had significantly improved the strength properties, permeability characteristic and compressibility behaviour of peat within 72 hours of curing. Moreover, reinforcement of peat medium using soil column method with 350 kg/m3 MUF-P binder had indicated that improvement of bearing capacity ratio (BCR) has increased proportionally to the increase of α from 14.1% to 23.6%. Validation using finite element modelling and analysis also had confirmed that improvement of load – settlement behaviour of treated peat soil using soil column method had a considerable agreement with physical modelling results.